FACTOR ASSOCIATED WITH LOW BACK PAIN COMPLAINTS IN TAILOR : LITERATURE REVIEW - Nurjannah, Besse; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
Background: An individual whose occupation is sewing is required to assume sedentary positions perform repetitive tasks while utilizing a single type of muscle. Sewing requires sharp concentration, coordination of posture and movements, and proper posture Method: Literature review A literature review was conducted using electronic data, specifically an original search of five periodicals. An electronic literature search is conducted utilizing databases such as PubMed and Google Scholar.